Mispatterning in the ommatidia of Apis mellifera pupae treated with a juvenile hormone analogue - Boleli, I. C.; Bitondi, MMG; Figueiredo, VLC; Simoes, ZLP (Wiley-Blackwell, 2001)
To further understand the function of morphogenetic hormones in honeybee eye differentiation, the alterations in ommatidial patterning induced by pyriproxyfen, a juvenile hormone (JH) analogue, were studied by scanning and transmission electron microscopy. Prepupae of prospective honeybee workers were treated with pyriproxyfen and the effects on ommatidial differentiation were described at the end of the pupal development. The results show that the entire ommatidia, i.e., the dioptric as well as the receptor systems, were affected by the JH analogue. The wave of ommatidial differentiation, which progresses from the posterior to the anterior region of the pupal eyes, was arrested. In treated pupae, the rhabdomeres only differentiated at the apical axis of the retinula, the secondary and tertiary pigment cells did not develop their cytoplasm protrusions, and the cone cell quartet did not pattern correctly. Simultaneously, an intense vacuolization was observed in cells forming ommatidia. In a previous study we showed that pyriproxyfen exerts an inhibition on pupal ecdysteroid secretion. In this sense, the arrested ommatidial differentiation in pyriproxyfen-treated pupae could be due to a secondary effect resulting from an alteration in pupal ecdysteroid titers. J. Morphol. 249:89-99, 2001. (C) 2001 Wiley-Liss, Inc.
Keywords: ommatidia; eye; Apis mellifera; juvenile hormone analogue; pyriproxyfen